Data on Indoor Air Quality (IAQ) in kindergartens with different surrounding activities - Abdullah S.; Abd Hamid F.F.; Ismail M.; Ahmed A.N.; Wan Mansor W.N. (Elsevier Inc., 2023)
Air quality; Carbon dioxide; Carbon monoxide; Housing; Indoor air pollution; Wind; Acceptable limit; Chemical and physical parameters; Chemical parameters; Indoor air quality; Kindergarten; Measurements of; Residential; Residential areas; Suspended particulates; Temperature and relative humidity; Thermal comfort